Social Phenomena 2015
DOI: 10.1007/978-3-319-14011-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Predicting Human Infectious Diseases

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…However, the predictions for SARS failed to match the data 3,5 . Over the subsequent 15 years, the scientific community developed a rich understanding for how social contact networks, variation in health-care infrastructure, the spatial distribution of prior immunity, etc., drive complex patterns of disease transmission [6][7][8][9][10][11] , and demonstrated that data-driven, dynamic, and or agentbased models can produce actionable forecasts [12][13][14][15][16][17] . Additionally, studies have demonstrated that predicting different components of outbreaks-e.g., the expected number of cases, pace, and tempo of cases needing treatment, demand for prophylactic equipment, importation probability, etc.-is feasible 3,13,[18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the predictions for SARS failed to match the data 3,5 . Over the subsequent 15 years, the scientific community developed a rich understanding for how social contact networks, variation in health-care infrastructure, the spatial distribution of prior immunity, etc., drive complex patterns of disease transmission [6][7][8][9][10][11] , and demonstrated that data-driven, dynamic, and or agentbased models can produce actionable forecasts [12][13][14][15][16][17] . Additionally, studies have demonstrated that predicting different components of outbreaks-e.g., the expected number of cases, pace, and tempo of cases needing treatment, demand for prophylactic equipment, importation probability, etc.-is feasible 3,13,[18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%
“…What remains an open question is whether the existing barriers to forecasting stem from gaps in our mechanistic understanding of disease transmission and low-quality data or from fundamental limits to the predictability of complex, sociobiological systems, i.e. outbreaks 4,6,7,[27][28][29][30] .…”
mentioning
confidence: 99%
“…So far, many efforts have been recently made to model virus spreading among computer network. Scholars mainly reference traditional infectious disease models (e.g., SI, SIS, SIR) in biological engineering [13]. And then they combine with the characteristics of computer virus to form computer virus spreading model [14,15].…”
Section: Related Workmentioning
confidence: 99%
“…Use of machine learning methods in understanding influenza dynamics are discussed in [19], [20], [21]. Additionally, review of existing influenza forecasting methods is discussed in [22], [23], [24].…”
Section: Introductionmentioning
confidence: 99%